CRIMINAL POLICY IN THE SHIPMENT OF FOREIGN FISHERMAN SHIPS IN THE PERSPECTIVE OF ECONOMIC ANALYSIS - Sri Dwi Retno Ningsih; Adi Sulistyono (UNISSULA, 2019)
The theft of fish resources in the Indonesian sea has caused huge losses to the fisheries sector in order to realize the welfare of the community. The Ministry of Maritime Affairs and Fisheries adopted a strict policy to eradicate illegal fishing through the act of sinking illegal fishing vessels. The magnitude of Indonesia's marine and fisheries wealth cannot be utilized optimally. Law enforcement is very important to deal with violations of law in Indonesian waters. One form of law enforcement is to implement policies such as sinking foreign vessels that steal fish in Indonesian waters while taking into account the efficiency and effect of deterrent effect on perpetrators of fish theft. The sinking policy of foreign fish-stealing vessels in Indonesian waters was pursued to secure the sea from looting by foreign parties. This policy will continue even though it could risk creating friction with the countries of origin of the foreign ship. Based on economic analysts on illegal fishing crimes, criminal fines can be used as an alternative to criminal punishment in addition to imprisonment in order to minimize operational costs of law enforcement.